Emphysematous Cystitis: A case Report - Islam, S. Serajul (Journal of Postgraduate Medical Institute, 2011)
We report a case of emphysematous cystitis, a 59 years old diabetic woman of vagus abdominal pain. Urinary frequency and high grade fever. On clinical examination, she was markedly dehydrated, ill looking obese lady with a temperature of 40.1 C and moderately tender over suprapubic area but urinary bladder was not palpable. urine dipstix was positive for blood and prtein. CT Scan of the abdomen revealed gas in and around the wall of urianry bladder.